Predicting academic staffs behaviour intention and actual use of blended learning in higher education: Model development and validation - Anthony, Bokolo Jnr.; Adzhar, Kamaludin; Awanis, Romli (Springer, 2021)
Blended Learning (BL) has been implemented by lecturers in higher educations for promoting effective pedagogical practices. However, intention to use and actual usage of BL by lecturers in higher education seems to be a major setback for successful BL implementation. Therefore, this study developed a model to examine the factors that influences lecturers’ behavioral intention and actual use of BL based on the Unified Theory of Acceptance and Use of Technology and Technological, Pedagogical and Content Knowledge model. Accordingly, survey questionnaire was employed to collect data from 544 academic staffs across universities, colleges, and polytechnics. Results indicate that performance expectancy, effort expectancy, and social influence significantly impact lecturers’ behavioral intention to use BL for teaching. Additionally, results confirm that facilitating condition positively influence actual BL usage. Likewise, technological, pedagogical, and content knowledge initiatives employed by lecturers in teaching positively influences actual BL usage. Results from multi-group analysis indicate that gender, age, experience, and voluntariness of use do not predict the behaviour of lecturers to use BL. Also, this study provides insights as to how higher education can enhance lecturers’ usage of BL to improve teaching effectiveness. This study provides a better understanding of lecturers’ views of knowledge in relation to course content, pedagogy, and technology use in improving teaching. The developed model can significantly be used by academic staffs to monitor and improve their current BL activities in measuring their knowledge about teaching regarding teaching improvement.